1979
DOI: 10.1530/jrf.0.0560081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prostaglandin F-2  on plasma levels of progesterone and pregnenolone in the hysterectomized guinea-pig

Abstract: Repeated injections of PGF-2 alpha were given to hysterectomized guinea-pigs. Within 12 h after the first injection, plasma progesterone levels were significantly reduced (P less than 0.001) and declined to less than 1 ng/ml by the 4th day after the end of PGF-2 alpha treatment. A decline in plasma levels of pregnenolone paralleled that of progesterone. PGF-2 alpha treatment did not affect the metabolic clearance rate of [3H]pregnenolone, but the converions of [3H]pregnenolone to [3H]progesterone was reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1979
1979
1982
1982

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This concentration of PGF-2a inhibits progesterone production by rat luteal cells (Thomas, Dorflinger & Behrman, 1978). The finding that this concentration of PGF-2a partly inhibited gonadotrophin-stimulated progesterone production by guinea-pig luteal cells is in agreement with observed inhibitory effects of this prostaglandin on the production of progesterone by guinea-pig corpora lutea in vivo (Dwyer & Church, 1979). Present observations are also in agreement with similar direct effects of PGF-2a on dispersed luteal cells (Thomas et al, 1978;Hall & Robinson, 1979) and luteal expiants (Lahav, Freud & Lindner, 1976;Khan et al, 1979) of the rat, and superfused preparations from pig corpora lutea (Watson & Maule-Walker, 1977).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This concentration of PGF-2a inhibits progesterone production by rat luteal cells (Thomas, Dorflinger & Behrman, 1978). The finding that this concentration of PGF-2a partly inhibited gonadotrophin-stimulated progesterone production by guinea-pig luteal cells is in agreement with observed inhibitory effects of this prostaglandin on the production of progesterone by guinea-pig corpora lutea in vivo (Dwyer & Church, 1979). Present observations are also in agreement with similar direct effects of PGF-2a on dispersed luteal cells (Thomas et al, 1978;Hall & Robinson, 1979) and luteal expiants (Lahav, Freud & Lindner, 1976;Khan et al, 1979) of the rat, and superfused preparations from pig corpora lutea (Watson & Maule-Walker, 1977).…”
Section: Discussionsupporting
confidence: 84%
“…There is considerable evidence to support the concept that prostaglandin (PG) F-2a is the uterine factor responsible for luteolysis in the guinea-pig (reviewed by Poyser, 1976). However, the luteolytic effect of PGF-2a in the guinea-pig, well established in vivo Dwyer & Church, 1979), has not, hitherto, been investigated in vitro, where PGF-2a may be added directly to suspensions of luteal cells.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in cholesterol esterase activity would reduce the availability of cholesterol for steroidogenesis while increasing the amount of cholesterol ester. This decrease in cholesterol esterase activity after 1 day of PGF-2a treatment, which would lead to an accumulation of cholesterol esters and a reduction in the availability of cholesterol for steroid synthesis, is reflected by the increase in lipid droplets after 2 days of PGF-2a treatment observed by Bagwell et al (1976) and by the declining plasma pregnenolone levels that we observed (Dwyer & Church, 1979).…”
Section: Discussionmentioning
confidence: 50%
“…In addition, the corpus luteum of the hysterectomized guinea pig has been found to be both ultrastructurally normal and steroidogenically active (Heap et al, 1967;Bagwell, Davies & Ruby, 1976). The reduction in plasma progesterone levels in hysterectomized guinea-pigs treated with PGF-2a is accompanied by decreased pregnenolone levels (Dwyer & Church, 1979), and an effect on 3ß-HSD activity was suggested since there was a reduction in the conversion of radioactive pregnenolone to progesterone in vivo. The results of the present study support this suggestion because the activities of 3 ß-HSD and cholesterol esterase in the ovary were reduced while the activities of cholesterol ester synthetase and PGF-2ct were not affected.…”
Section: Discussionmentioning
confidence: 99%